Pasar Modal Dan Pengaruhnya Terhadap Perekonomian Di Indonesia - Dewi Lubis, Putri Kemala; Br Silalahi, Hanna Hotmian; Fitria Sinaga, Anisa; Nidia Sapma, Putri; Sitio, Veranita (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The capital market is a financial instrument that plays an important role in supporting and disrupting economic progress in a country. This research aims to find out how much influence the capital market has in advancing the economy in Indonesia and what challenges and obstacles are experienced in its implications. The research method used is a qualitative research method using a literature study approach. An overview of several relevant articles from the Sinta indexed journal shows that the capital market is closely related to economic growth in a country. This study clearly states that for a country's economy, the capital market plays a dual role as a means of providing funding for both government and private businesses and a means for investors who wish to invest their capital in a company to gain profits. In conclusion, the capital market is a bridge for society which also contributes to supporting the economy in a country.